The Seroprevalence of Chlamydia Infection in Sheep in Shanxi Province, China - Chen-Xu Li; Jin Gao; Sheng-Rong Shi; Wen-Wei Gao; Xing-Quan Zhu; Yu-Ping Lei; Yu Zhang; Wen-Bin Zheng (Veterinary Sciences, 2022)
Chlamydia, an obligate intracellular bacterium, can cause chlamydiosis in humans and animals worldwide and also leads to serious economic losses to the sheep industry. However, the information on Chlamydia infection in sheep was limited in Shanxi Province, northern China. In the present study, a total of 984 serum samples of sheep were collected from 11 regions in Shanxi Province, northern China in the autumn of 2020. The antibodies against Chlamydia and Chlamydia abortus were examined by the indirect hemagglutination assay (IHA) and indirect enzyme-linked immunosorbent assay (ELISA), respectively. The result showed that 351 (35.67%, 95% CI 32.68–38.66) of 984 serum samples were positive for Chlamydia, and the seroprevalence ranged from 6.67% to 70.79% among the different regions. In addition, antibodies to C. abortus infection were detected in 78 (7.93%, 95% CI 6.24–9.61) of 984 serum samples, and the seroprevalence ranged from 6.24% to 14.81% among the different regions. This is the first report on the seroprevalence of Chlamydia and C. abortus in sheep in Shanxi province, northern China. The findings provide baseline information for preventing and controlling Chlamydia infection in sheep in Shanxi Province, China.